“In a Satisfactory, Organized, and Scientific Fashion”: Sex Education and Ontario’s Ministry of Education, 1955–1979 - Brenyo, Brent (Ontario History)

(untitled) (The Ontario Historical Society, 2022)
Sex education in Ontario during the second half of the twentieth century was shaped by two policymaking paradigms: methodological rationalism and incrementalism. Structural transformations occurring within the modern liberal state at mid-century resulted in the emergence of technocratic policymaking, which allowed policymakers to employ a methodology of calculated rationalism. Technocratic policymaking—which intertwined policy formulation with the empirical aspects of socio-sexual problems—allowed educational bureaucrats to produce defensible policy based on quantifiable problems. However, interest group pluralism dictated that they also practice interest-group-directed incrementalism. These two decision-making models allowed the Ministry of Education to introduce sex education progressively between 1955 and 1979 in an attempt to ameliorate socio-sexual problems. As a result, sex education—under conditions of liberal modernity—was cumulatively institutionalized as part of Ontario public schooling.